Bridging the gap between pregnancy loss research and policy and practice: insights from a qualitative survey with knowledge users - Marita Hennessy; Keelin O'Donoghue (BMC, 2024)
Abstract Background The loss of a pregnancy or the death of baby around the time of their birth can have profound impacts on parents, families and staff involved. There is much opportunity to enhance the systematic uptake of evidence-based interventions to enhance service provision, lived experiences and outcomes. Challenges exist to translating pregnancy loss research evidence into policy and practice, however. Pregnancy loss remains a neglected area of research and resourcing and is steeped in stigma. While barriers and facilitators to the use of research evidence by decision-makers in public health and health services are well documented, we aimed to better understand the factors that influence the translation of pregnancy loss research into practice and policy. Methods We conducted a qualitative online survey of pregnancy loss research knowledge users in Ireland, identified through our clinical and academic networks, between January and March 2022. The survey comprised ten questions, with three closed questions, informed by the Knowledge Translation Planning Template©. Questions included who could benefit from pregnancy loss research, perceived barriers and facilitators to the use of research evidence and preferred knowledge translation strategies. We analysed data using reflexive thematic analysis. Results We included data from 46 participants in our analysis, from which we generated two central themes. The first-'End the silence; stigma and inequality around pregnancy loss to enhance awareness and understanding, public health and services and supports'-addresses issues related to the stigma, sensitivities and silence, lack of awareness and understanding, and lack of relevance or priority afforded to pregnancy loss. The second theme-'Use a range of tailored, accessible approaches to engage a large, diverse range of knowledge users'-highlights the need to use relevant, accessible, and engaging information, resources or materials in knowledge translation efforts, and a variety of tailored approaches to suit different audiences, including materials, workshops/webinars, media, knowledge brokers and champions or opinion leaders. Conclusions Our analysis provides rich insights into the barriers and facilitators to knowledge translation in the field of pregnancy loss research. We identified key strategies that can be used to inform knowledge translation planning in Ireland, and which have international applicability.